Effective communication in Audits: A linguistic Perspective - Rasyki, Adrian; Lumban Gaol, Lasando (PERSPEKTIF, 2025)
This study investigates the dynamics of auditor-client communication to establish a balance between technical and non-technical language, communication skills, and satisfaction levels. The research adopts a quantitative analysis in combination to explore how these factors impact communication effectiveness. The study's respondents are 60 auditors, including expert auditors from the BPKP Indonesian Financial and Development Supervisory Agency and P2UPD auditors from the Ministry of Home Affairs, who were chosen for their relevant expertise. The study used a structured questionnaire to examine the frequency and context of technical and non-technical language usage, communication skills, and satisfaction levels. Data were analyzed using multiple linear regression, a statistical method to assess how independent variables influence communication outcomes. Technical language, such as "materiality thresholds" and "variance analysis," helps clarify complex concepts but can obstruct client comprehension when used excessively. Non-technical language, such as general terms like "acceptable margin of error," improves clients' comprehension and engagement in communication, particularly for clients who are not technically savvy. Auditors' communication skills, especially listening, speaking, and interpersonal interaction, were the strongest predictors of effective communication. Communication satisfaction also played a crucial role in building trust and smoothing interactions. This study concluded that balancing technical and non-technical language, honing communication skills, and prioritizing satisfaction are essential for enhancing audit outcomes. However, this research focuses on public-sector auditors in Indonesia, which may limit generalizability to other sectors. Recommendations include training auditors in adaptive communication strategies and implementing feedback mechanisms to sharpen their approach. These results contribute to the literature by combining linguistic and audit practice perspectives to provide actionable insights into better communication strategies, improving audit processes, and informing policy improvements.